The effectiveness of e-learning among students / Haziq Zuhair Mohamad Ismail - Mohamad Ismail, Haziq Zuhair (2024)
In recent years, education has been reshaped by the use of both technologies and particularly the use of the internet. e-Learning, or also known as online classes or Online Distance Learning (ODL), have emerged as one of components in this educational transformation. Due to the expanding accessibility of the internet and its integration with education, the term e-learning has arisen. It commonly denotes the development of learning experiences through the utilisation of online technologies (Chopra et al., 2019). Additionally, the global outreach of online classes supports the argument of reduced educational disparity. According to a report by the World Economic Forum (2016), online education has the potential to make advanced learning accessible to a broader population, including those in developing nations, potentially reducing the educational divide. Numerous countries have adopted online distance learning as an alternative teaching method to curb the spread of the disease (Pathak & Singh 2023). The adoption of online distance learning reflects the adaptability of educational systems in response to external challenges. It indicates a willingness to explore alternative teaching approaches when faced with various concerns such as health related.